Genome-wide association study for carcase traits in spent hens at 72 weeks old. Issue 1 (2nd January 2019) - Ma, Meng; Shen, Manman; Qu, Liang; Dou, Taocun; Guo, Jun; Hu, Yuping; Lu, Jian; Li, Yongfeng; Wang, Xingguo; Wang, Kehua
Abstract: To determine the genetic architecture underlying spent hen carcase traits, especially in late laying, we used 1512 hens generated from Dongxiang Blue-Shelled and White Leghorn chickens to implement genome-wide association studies by high-density arrays. A total of 266 loci that mapped to ( Gallus gallus chromosome) GGA1, GGA4 and GGA27 were detected. After linkage disequilibrium analysis, five SNPs were considered as candidate markers because they located on or near the genes CKAP2, RB1, CCKAR, NCAPG and IGF2BP1 . The heritability of all carcase traits was high, and SNP effects ranged from 3.24% to 8.72%. These findings provide new insights into the genetic architecture of carcase traits in spent layer hens. Highlights: Resource population generated from two breeds were used to measure carcass traits in spent hens. A total of 266 loci association with carcass traits located on GGA1, GGA4, and GGA27. Five putative candidate genes CKAP2, RB1, CCKAR, NCAPG and IGFBP1 were obtained after gene annotation.